Optimized automated radiosynthesis of 18F-JNJ64413739 for purinergic ion channel receptor 7 (P2X7R) imaging in osteoporotic model rats - Lu, Yingtong; Cui, Yan; Hou, Lu; Jiang, Yuanfang; Shang, Jingjie; Wang, Lu; Xu, Hao; Ye, Weijian; Qiu, Yang; Guo, Bin (Frontiers in Pharmacology, 2024)
ObjectiveTo optimize the automated radiosynthesis of the purinergic ion channel receptor 7 (P2X7R) imaging agent 18F-JNJ64413739 and evaluate its potential for brain imaging in osteoporotic model rats.MethodsA more electron-deficient nitropyridine was employed as the labeling precursor to facilitate the 18F-labeling. The radiosynthesis was conducted on an AllinOne synthesis module, and followed by purification via high-performance liquid chromatography (HPLC). The resulting 18F-JNJ64413739 was subjected to quality control tests. Small-animal PET/CT imaging studies were performed in sham and osteoporotic model rats.ResultsThe optimized automated radiossynthesis of 18F-JNJ64413739 was successfully completed in approximately 100 min with non-decay-corrected radiochemical yield of 6.7% ± 3.8% (n = 3), >97% radiochemical purity and >14.3 ± 1.3 GBq/μmol molar activity. The product met all clinical quality requirements. 18F-JNJ64413739 PET/CT imaging showed revealed significantly higher radioactivity uptake in various brain regions of the osteoporotic model rats compared to sham control group.ConclusionWe successfully optimized the automated radiosynthesis of 18F-JNJ64413739. The resulting tracer not only met clinical quality requirements but also demonstrated potential for clinical application in the diagnosis of osteoporosis, as evidenced by higher radioactivity uptake in various brain regions of osteoporotic model rats compared to normal controls.